2012
DOI: 10.1186/1471-2458-12-344
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of physical activity monitoring and distance counseling in an occupational setting – Results from a randomized controlled trial (CoAct)

Abstract: BackgroundLack of physical activity (PA) is a known risk factor for many health conditions. The workplace is a setting often used to promote activity and health. We investigated the effectiveness of an intervention on PA and productivity-related outcomes in an occupational setting.MethodsWe conducted a randomized controlled trial of 12 months duration with two 1:1 allocated parallel groups of insurance company employees. Eligibility criteria included permanent employment and absence of any condition that riske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 34 publications
0
81
0
1
Order By: Relevance
“…Among the randomized studies, 16 were largely internet-based[13][28], while the other 2 were multi-component studies[29], [30]. Similarly, 2 of the 10 interventions (11 studies) in the pre-post group had multiple components[31], [32], while the others were largely internet-based [12], [33][40].…”
Section: Resultsmentioning
confidence: 99%
“…Among the randomized studies, 16 were largely internet-based[13][28], while the other 2 were multi-component studies[29], [30]. Similarly, 2 of the 10 interventions (11 studies) in the pre-post group had multiple components[31], [32], while the others were largely internet-based [12], [33][40].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported on outcomes related to physical activity [2940] and 11 on outcomes related to weight [2729,3137,39]. Four trials were conducted with older adults; five with overweight, obese, or sedentary adults; three with participants with a chronic medical illness (e.g., chronic obstructive pulmonary disease, metabolic disease, diabetes); and two with healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Articles had to include at least one term from each of the filters in the title, abstract, or measure, but did not report sufficient data for us to be able to compute an effect size and this information could not be obtained by emailing the author(s) (e.g., Reijonsaari et al, 2012). Eighty one studies (13%) were excluded because they did not randomly assign adult participants to an intervention condition designed to promote self-monitoring of goal progress (e.g., Graham, Cha, Cobb, Fang, Niaura, & Mushro, 2013; Te Velde, Wind, PerezRodrigo, Klepp, & Brug, 2008).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Finally, studies had to include a measure of behavior(s) (e.g., step count) or outcome(s) (e.g., levels of glycated haemoglobin [HbA1c], weight) in the wake of the intervention. 1 The sample of studies was generated via a computerized search of social scientific databases (those accessed by Web of Knowledge 2 , as well as UMI Dissertation Abstracts).Three search filters were used, one for randomized control trials (random* AND intervention or random* AND experiment*) 3 , one for progress monitoring designed to reflect different terms for self-monitoring and methods that interventions might use to invoke progress monitoring (monitor* OR progress OR track OR diary OR website OR Personal Digital Assistant OR Phone OR pedometer OR meter OR self-weigh*), and one filter for the dependent variable (goal OR behav* OR outcome OR perform* OR consum*).Articles had to include at least one term from each of the filters in the title, abstract, or measure, but did not report sufficient data for us to be able to compute an effect size and this information could not be obtained by emailing the author(s) (e.g., Reijonsaari et al, 2012). Eighty one studies (13%) were excluded because they did not randomly assign adult participants to an intervention condition designed to promote self-monitoring of goal progress (e.g., Graham, Cha, Cobb, Fang, Niaura, & Mushro, 2013; Te Velde, Wind, PerezRodrigo, Klepp, & Brug, 2008).…”
mentioning
confidence: 99%